The empire strikes back - MacNeil, Robert (Sydney, NSW. : BBC Education & Training, 1986)
The video poses the question'Will English continue as the global tongue?' It also focuses on some of the most widely known examples of'New English'
Title from data sheet
Backup available in VHS
Keywords: Pidgin English